Character Psychological Features Research of Ukrainian Antarctic Expeditions Staff - E. Miroshnichenko (Ukrainian Antarctic Journal, 2013)
The article deals with the study of psychological character features in wintering personnel (Ukrainian Antarctic station Academik Vernadsky (Period 2011–2013)), emphasizes the role of person psychological qualities in the selection of team members for polar expeditions.